The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1136/bmjopen-2020-039566
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric properties of the Chinese version of the TeamSTEPPS teamwork perceptions questionnaire to measure teamwork perceptions of Chinese residents: a cross-sectional study

Abstract: ObjectivesThe purpose of this research was to evaluate the psychometric properties of the TeamSTEPPS Teamwork Perception Questionnaire (T-TPQ) among the Chinese residents.DesignCross-sectional study.SettingA clinical hospital of the China Medical University in Liaoning Province, China.ParticipantsA total of 664 residents were enrolled in this research. The valid response rate was 83.0% (664 of 800 residents).Main outcome measuresInternal consistency and test–retest reliability were used to assess the reliabili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
11
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(18 citation statements)
references
References 50 publications
4
11
3
Order By: Relevance
“…The five-factor IR-T-TPQ showed satisfactory internal consistency, with a total Cronbach's alpha of 0.96, above the recognized threshold of 0.70. The result of reliability was in line with the prior validation studies of the T-TPQ in other countries, such as Korea [9], Norway [10,11], China [15], the USA [32], and the original English version [8]. In contrast, in the Swedish study by Hall-Lord et al, Cronbach's alpha values were low in Mutual Support and Communication [13].…”
Section: Discussionsupporting
confidence: 85%
See 4 more Smart Citations
“…The five-factor IR-T-TPQ showed satisfactory internal consistency, with a total Cronbach's alpha of 0.96, above the recognized threshold of 0.70. The result of reliability was in line with the prior validation studies of the T-TPQ in other countries, such as Korea [9], Norway [10,11], China [15], the USA [32], and the original English version [8]. In contrast, in the Swedish study by Hall-Lord et al, Cronbach's alpha values were low in Mutual Support and Communication [13].…”
Section: Discussionsupporting
confidence: 85%
“…The RMSEA was 0.059, and χ2/df was below 3. According to the recommendations for CFA, these goodness-of-fit indexes of CFA indicated an acceptable fit with the original construct [29], and the result was in agreement with the previous validation Chinese study of the T-TPQ (RMSEA = 0.059) [15]. Some previous studies that also reported acceptable RMSEA values include the Norwegian study by Ballangrud et A = 0.062) [14], and the USA study by Keebler et al…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations